Kinerja Karyawan Ditinjau Dari Insentif, Lingkungan Kerja dan Work Life Balance pada KSPPS BMT Hira Sragen - Reza Rachmawati; Siti Maryam; Fithri Setya Marwati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The purpose of this study is to determine the effect of insentives, work environment, and work life balance on employe performance at KSPPS BMT Hira Sragen. This researc method uses a descriptive quantitative research design. The population in this study is the employe of KSPPS BMT Hira Sragen, with a sample size of 62 respondents. Data analysis was performed using a multiple linear regression analysis, coeeficient of determination (R2), model feasibility test (F) and hypothesis test (t). The result of this study show that insentives, work environment and woek life balance have a positive and significant effect on employee performance both partially at KSPPS BMT Hira Sragen.